2012
DOI: 10.1111/j.1754-9485.2012.02464.x
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life using intensity‐modulated radiation therapy for post‐prostatectomy radiotherapy

Abstract: This report on HRQoL following post-prostatectomy IMRT demonstrates no variation in mean scores in any domain and only 1.6% of patients reporting a greater than 20-point deterioration between baseline and 15-24 months in bowel function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
4
11
0
Order By: Relevance
“…However, pre-RT baseline status in the GI, GU, and sexual domains fully recovered between 3 months and 1 year after therapy, remaining stable for at least 5 years. Two previous series have shown stability of HRQOL outcomes at 2 years after postoperative IMRT without image guidance, 34,35 and we provide evidence this is maintained with longer follow-up. The impact of postprostatectomy RT in sexual function represents a major concern influenced by low residual function after surgery.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, pre-RT baseline status in the GI, GU, and sexual domains fully recovered between 3 months and 1 year after therapy, remaining stable for at least 5 years. Two previous series have shown stability of HRQOL outcomes at 2 years after postoperative IMRT without image guidance, 34,35 and we provide evidence this is maintained with longer follow-up. The impact of postprostatectomy RT in sexual function represents a major concern influenced by low residual function after surgery.…”
Section: Discussionsupporting
confidence: 68%
“…As shown in Table 4, the literature regarding patientreported outcomes related to treatment toxicities and HRQOL in the postprostatectomy setting is limited. [32][33][34][35] Importantly, this study demonstrates a transient negative impact in HRQOL. However, pre-RT baseline status in the GI, GU, and sexual domains fully recovered between 3 months and 1 year after therapy, remaining stable for at least 5 years.…”
Section: Discussionmentioning
confidence: 87%
“…In four other studies [6,1214], the psychological domain of QOL improved during RT. In contrast, in five studies [1519], the physical, psychological, and social domains of QOL did not change during patients’ RT. Only two small prospective studies were found that assessed the spiritual domain of QOL in patients undergoing RT [20,21].…”
Section: Introductionmentioning
confidence: 84%
“…Although SRT may achieve biochemical responses, there is no Level-1 evidence that shows a survival benefit [2,3]. Therefore, it is important to understand the additional treatment burden associated with SRT and its effect on health-related quality of life (HRQoL) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%